2004
DOI: 10.1539/joh.46.109
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Semen Indices in Insecticide Sprayers

Abstract: A Survey of Semen Indices in InsecticideSprayers: Michihiro Kamijima, et al. Department of Occupational and Environmental Health, Nagoya University Graduate School of Medicine-This study aims at clarifying the semen indices of insecticide sprayers who are exposed mainly to organophosphorus and pyrethroid insecticides. Eighteen male sprayers out of 54 working for 9 companies in central Japan and 18 age-matched students or medical doctors as unexposed controls participated in detailed reproductive check-ups cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 37 publications
(47 reference statements)
7
59
0
1
Order By: Relevance
“…This study also revealed a decrease in the percentage of motile sperm in rats treated with dimethoate. A similar result was recorded by Kamijima et al (2004), among pesticide applicators regularly exposed to organophosphates. This could be due to low production of epididymal proteins.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study also revealed a decrease in the percentage of motile sperm in rats treated with dimethoate. A similar result was recorded by Kamijima et al (2004), among pesticide applicators regularly exposed to organophosphates. This could be due to low production of epididymal proteins.…”
Section: Discussionsupporting
confidence: 86%
“…A decrease in epididymal sperm density was also reported by Thonneau et al (1996) in rats gavaged with quinalphos; by Sobarzo and Bustos-Obregeon (2000); Bustos-Obregon and Gonzallez Harmanzaba (2003) in rats that received parathion and Kamijima et al (2004) among pesticide applicators. This depreciation in epididymal sperm concentration may be related to Science Publications AJPT inhibition of the biosynthesis of testosterone as mentioned above or to the cessation of the release of FSH and LH in the brain.…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, a growing need for the assessment of pyrethroid pesticide exposure has been recognized. Under current exposure levels in the studied population, medical examinations including routine clinical blood tests showed no exposure-related hazardous effects on the health status of PCOs, although a previous study identified a slight deterioration in semen quality in work associated with spraying 21) . All synthetic pyrethroids are rapidly metabolized by hydrolytic cleavage to form their corresponding metabolites, 1) acid moieties such as cis-3-(2,2-dibromovinyl)-2,2-dimethylcyclopropane-1-carboxylic acid or cis-and trans-3-(2,2-dichlorovinyl)-2,2-dimethylcyclopropane-1-carboxylic acid, and 2) alcohol m o i e t i e s w h i c h a r e o x i d i z e d t o 4 -f l u o r o -3 -phenoxybenzoic acid or 3-PBA.…”
Section: Discussionmentioning
confidence: 65%
“…59,60) Recent several non-occupational studies have suggested that environmental PYR exposure might be associated with circulating hormone levels and semen parameters (Table 4). Urinary PYR metabolites were measured as a biomarker of PYR exposure in each paper.…”
Section: Results Unitsmentioning
confidence: 99%